Diagnostic imaging in congenital diaphragmatic hernia, more than just a diaphragmatic defect: a narrative review - De Barbieri Magnone, Florencia (2023)
Congenital diaphragmatic hernia is a relatively common major malformation with a life-threatening prognosis. This condition involves an abnormal development of the diaphragm, lungs, and particularly the blood vessels and other related structures. Images of these structures are essential for diagnosis, pre- and postoperative assessment, and serial monitoring. In the prenatal period, ultrasound plays a fundamental role in early diagnosis; ultrasound and magnetic resonance allow evaluation of the degree of lung hypoplasia and the presence of associated anomalies to predict survival and the possible need for more complex strategies such as extracorporeal membrane oxygenation (ECMO) in the perinatal period. In the postnatal period, portable radiography and ultrasound are essential in the serial assessment of children, whether they receive supportive therapies such as invasive mechanical ventilation, ECMO, or surgery. Knowledge of the pathophysiology and radiological manifestations of each of these phases is essential to allow appropriate assessment, optimize treatment, and ultimately improve the survival of these children.